THE RESPONSE OF THE MEDIUM FIBER COTTON VARIETY PIDOZERSKY 4 TO THE SEEDING RATE AND ROW WIDTH UNDER DIFFERENT CONDITIONS OF SOIL MOISTURE IN THE SOUTHERN STEPPE OF UKRAINE - Raisa VOZHEHOVA; Vira BOROVYK; Yuriy STEPANOV; Iryna BIDNYNA; Liubov BOIARKINA; Olena PILIARSKA; Viktor SHARII; Tetyana KHOMENKO; Olesia DROBIT (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article presents the results of studying the reaction of the early maturing medium-fiber cotton variety Pidozerskyi 4 to the sowing rate and row width under different conditions of moisture supply in the Southern Steppe of Ukraine. The scheme of the experiment included soil moisture conditions: natural moisture and watering at 70% of the lowest moisture content (LM); row width 30, 60, 90 cm; sowing rate of 250, 300 and 350 thousand pieces/ha. Studies have shown that the formation of the number of pods on a plant that opened before harvesting was significantly influenced by the rate of seed sowing, with an increase in which the indicators of the number of pods decreased on average by 43.9% in the experiment, and regardless of the conditions of soil moisture and width row spacing. The variability of the effective signs of the mass formation of the boll of pre-freeze raw cotton depended by 25.0% on the humidification conditions, by 15.0% - on the width of the rows, and by 16.0% - on the seeding rate; yield of domestic raw cotton - by 66.0% from the conditions of wet supply, by 3.0% - from the width of the rows and by 9.0% - from the sowing rate. The significant influence of irrigation on the yield formation of frozen raw cotton was determined. The increase in yield on irrigated plots at the seeding rate of 300,000 units/ha was: for row widths of 30 cm – 17%, for 60 cm – 18%, for 90 cm – 22%, compared to non-irrigated options. Raw cotton production is highly effective, the profitability level is 63-69%.